2011
DOI: 10.1194/jlr.m013342
|View full text |Cite
|
Sign up to set email alerts
|

Integrating expression profiling and whole-genome association for dissection of fat traits in a porcine model

Abstract: This article is available online at http://www.jlr.org lated to body composition, leanness, and obesity. Traits related to fatness are important not only as economic factors in pork production but also because of their association with serious diseases in humans ( 1, 2 ). Pigs share many similarities with humans in physiology and genomes and, therefore, provide a good model to study the genetic determination of complex traits ( 3 ). The study of a porcine model is benefi cial because a number of fatness traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 55 publications
3
37
0
Order By: Relevance
“…We observed a highly significant enrichment of transcripts associated with LXR/RXR, PXR/RXR and FXR/RXR activation among those transcripts correlated with biochemical and body composition traits, consistent with a previous study on liver expression relation to body composition in other pig breeds6. These pathways play an important regulatory role in the metabolism of carbohydrates, fatty acids and cholesterol60.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed a highly significant enrichment of transcripts associated with LXR/RXR, PXR/RXR and FXR/RXR activation among those transcripts correlated with biochemical and body composition traits, consistent with a previous study on liver expression relation to body composition in other pig breeds6. These pathways play an important regulatory role in the metabolism of carbohydrates, fatty acids and cholesterol60.…”
Section: Discussionsupporting
confidence: 91%
“…Knowledge of the position of the analyzed genes and markers enables the differentiation of cis- and trans-eQTLs4. We have previously shown that the detection of trait-dependent expressed genes in a relevant tissue facilitates the identification of genes associated with complex traits, such as muscle and meat properties and coping behaviors; these genes represent strong candidate genes56. Studies of eQTLs in the human liver have led to the identification of genes associated with clinical phenotypes and provide a foundation for pharmacogenomics7.…”
mentioning
confidence: 99%
“…In agreement, biological functions related to glucose metabolism and lipid accumulation, as concentration of lipid , concentration of fatty acid and concentration of triacylglycerol (Fig 4), were enriched in growing IB pigs. Moreover, the LPS/IL-1 Mediated Inhibition of RXR pathway, enriched in those pigs was reported to positively correlate with fat area [85]. …”
Section: Discussionmentioning
confidence: 99%
“…37 It has been reported that the reduction of proteins related to the LPS/IL-1–mediated inhibition of RXR function pathway can lead to impaired metabolism, transport or biosynthesis of lipid, cholesterol, bile acid, and xenobiotics. 38,39 In APAs, genes related to this pathway were mainly upregulated, suggesting perhaps a role in the metabolism, transport, and biosynthesis of cholesterol, a key precursor of aldosterone. On the contrary, genes associated with this pathway were downregulated in ZG (Table S16), suggesting decrease of corticosteroid synthesis, which is in agreement with our previous finding of ZG selective genes regulating aldosterone negatively and the low patchy staining of CYP11B2 in ZG.…”
Section: Discussionmentioning
confidence: 99%